The Influence Of Women Leaders And Their Leadership Style On Employee Engagement Through Talent Management As Mediating Variable - et.al, Dwi Putra Budi Setia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to investigate the impact of transformational & transactional leadership style towards employee engagement mediated by talent management practices among subordinates with woman as their direct superiors. As the research was conducted during pandemic Covid-19, questionnaires were distributed through online. The method of purposive sampling was adopted to make sure that certain criteria was met before the respondents were deemed to be eligible in filling up the questionnaires. In the end, 117 questionnaires were returned, in which 64% came from manufacturing and mineral industries (majority in oil and gas), while another 36% came from service industries (majority from public sector and trading). The analysis of multiple regression was performed towards the data in addition to use the mediation analysis proposed by Baron & Kenny. The study found that both leadership style was indeed practiced by women leaders. However, results suggested that partial mediation exists in the relationship between transformational leadership style towards employee engagement. While full mediation was supported in the relationship between transactional leadership style towards employee engagement.